High sensitization efficiency and energy transfer routes for population inversion at low pump intensity in Er organic complexes for IR amplification - Hu, J. X. (2018)
Organic erbium complexes have long been of interest due to their potential for using the strong absorption into the organic to sensitise the erbium emission. Despite this interest there is remarkably little quantitative information on how effective the approach is and the discussion of the energy transfer mechanism is generally vague. Here we accurately quantify the sensitisation as a function of excitation pump density and model it using a rate equation approach. As a result, we can calculate the degree of population inversion for the erbium ions as a function of the pump intensity. We demonstrate that even when we increase the erbium concentration in the films from ~10 to ~80% we find a relatively small decrease in the sensitisation which we attribute to the large (>20 Å) Förster radius for the sensitisation process. We show that we can obtain population inversion in our films at very low pump powers ~600 mW/cm2. The calculated Förster radius for the organic erbium complexes suggests design rules for energy transfer between antennas and erbium ions in molecular systems and hybrid organic-inorganic nanoparticles.